Toll-like receptor 8 agonists improve NK-cell function primarily targeting CD56brightCD16− subset - Enrico Maggi; Giovanni Scambia; Anna Fagotti; Lorenzo Moretta; Andrea Pelosi; Irene Veneziani; Valentina D'Oria; Claudia Alicata; Nadine Landolina; Biancamaria Ricci (Journal for ImmunoTherapy of Cancer)
Background Toll-like receptors (TLRs) are pattern-recognition sensors mainly expressed in innate immune cells that directly recognize conserved pathogen structures (pathogen-associated molecular patterns-PAMPs). Natural killer (NK) cells have been described to express different endosomal TLRs triggered by RNA and DNA sequences derived from both viruses and bacteria. This study was addressed to establish which endosomal TLR could directly mediate NK activation and function after proper stimuli. It was also important to establish the most suitable TLR agonist to be used as adjuvant in tumor vaccines or in combined cancer immunotherapies.Methods We assessed endosomal TLR expression in total NK cells by using RT-qPCR and western blotting technique. In some experiments, we purified CD56brightCD16− and CD56dimCD16+ cells subsets by using NK Cell Isolation Kit Activation marker, cytokine production, CD107a expression and cytotoxicity assay were evaluated by flow cytometry. Cytokine release was quantified by ELISA. NK cells obtained from ovarian ascites underwent the same analyses.Results Although the four endosomal TLRs (TLR3, TLR7/8, and TLR9) were uniformly expressed on CD56brightCD16− and CD56dimCD16+ cell subsets, the TLR7/8 (R848), TLR3 (polyinosinic-polycytidylic acid, Poly I:C) and TLR9 (ODN2395) ligands promoted NK-cell function only in the presence of suboptimal doses of cytokines, including interleukin (IL)-2, IL-12, IL-15, and IL-18, produced in vivo by other environmental cells. We showed that R848 rather than TLR3 and TLR9 agonists primarily activated CD56brightCD16− NK cells by increasing their proliferation, cytokine production and cytotoxic activity. Moreover, we demonstrated that R848, which usually triggers TLR7 and TLR8 on dendritic cells, macrophages and neutrophils cells, activated CD56brightCD16− NK-cell subset only via TLR8. Indeed, specific TLR8 but not TLR7 agonists increased cytokine production and cytotoxic activity of CD56brightCD16− NK cells. Importantly, these activities were also observed in peritoneal NK cells from patients with metastatic ovarian carcinoma, prevalently belonging to the CD56brightCD16− subset.Conclusion These data highlight the potential value of TLR8 in NK cells as a new target for immunotherapy in patients with cancer.